Sulforaphane suppresses lipopolysaccharide‐ and Pam3CysSerLys4‐mediated inflammation in chronic obstructive pulmonary disease via toll‐like receptors - Xiaoli Zeng; Xiaoju Liu; Hairong Bao (FEBS Open Bio, 2021)
Chronic obstructive pulmonary disease (COPD) is a progressive inflammatory disease of the airway that represents a large global disease burden. Inflammation is a prominent feature of COPD and represents an important target for treatment. Toll‐like receptors (TLRs) are pattern recognition receptors that detect invading microorganisms and nonmicrobial endogenous molecules to trigger inflammatory responses during host defense and tissue repair. The TLR signaling pathway is closely linked to the pathogenesis of COPD. Sulforaphane (SFN), an isothiocyanate derived from cruciferous vegetables, is well known for its anti‐inflammatory activities. However, the molecular function of SFN in inhibition of COPD inflammation has yet to be fully elucidated. In this study, we investigated the effects of SFN on lipopolysaccharide (LPS)‐ or Pam3CysSerLys4 (Pam3CSK4)‐induced inflammation in monocyte‐derived macrophages (MDMs) from patients with COPD. MDMs from patients with COPD showed higher expression levels of TLR2, TLR4 and downstream myeloid differentiation factor 88 (MyD88) than healthy controls, along with increased secretion of interleukin‐6 (IL‐6) and tumor necrosis factor‐α (TNF‐α) (P < 0.05). Stimulation with TLR ligands (Pam3CSK4 and LPS) up‐regulated the levels of TLR2, TLR4 and MyD88 in MDMs from patients with COPD and induced the release of IL‐6 and TNF‐α (P < 0.05). Pretreatment of MDMs from patients with COPD with SFN significantly suppressed Pam3CSK4‐ or LPS‐induced TLR2, TLR4 and MyD88 expression, along with a reduction in the production of IL‐6 and TNF‐α (P < 0.05). Collectively, these data indicate that SFN exerts its anti‐inflammatory activity in COPD by modulating the TLR pathway. SFN may represent a potential therapeutic agent for the treatment of COPD.